LIQUIDITY MANAGEMENT FRAMEWORKS AND THEIR ROLE IN ENHANCING COMMERCIAL BANKS' CAPACITY TO ABSORB RISK - Muzna Ayal Fttnan (PT. Antis International Publisher, 2026)
Objective : the objective of this research is to analyze the role of the liquidity management framework in enhancing the ability of Iraqi commercial banks to absorb risk. Method : the study used a descriptive-analytical approach, using a questionnaire as the primary data collection instrument, which was applied to a sample of 160 employees of five Iraqi commercial banks: Al-Rafidin, Al-Rashid, Baghdad, Ashur and Trade Bank of Iraq. Results : the findings revealed a strong positive correlation between liquidity regime and risk absorption capacity (r = 0.742) indicating that the combined dimensions of liquidity regime explain 61.6% of the variation in risk absorption capacity. Furthermore the results showed that the procedural dimension had the strongest effect (β = 0.412) followed by the structural dimension (β = 0.281) and the supervisory dimension (β = 0.195). Novelty : based on these results, the study recommends developing internal liquidity pricing systems that integrate liquidity costs, establishing specialized liquidity risk committees, implementing advanced stress testing programs, creating independent internal liquidity control units and investing in improving liquidity information management systems.